(untitled) (Revista de Biblioteconomia de Brasília, 2001)
BORGMAN, Christine L. From Gutenberg to the global information infrastructure: access to information in the networked world. Cambridge,Mass.: MIT Press, 2000. 324 p. (Digital libraries and electronic publishing).